ANALISIS KOMUNIKASI INTERPESONAL GURU DENGAN MENGGUNAKAN MEDIA PECS BAGI ANAK BERKEBUTUHAN KHUSUS PADA YAYASAN ANAK EMAS DENPASAR - cahayana, rosmini (Jurnal Ilmiah Dinamika Sosial, 2018)
ABSTRACTKeywords: interpersonal communicationThis study entitled Analysis of Interpersonal communication of teachers byusing media pecs for children with special needs in the foundation of golden childrenof Denpasar. The purpose of this study was to find out how to communicate withchildren with special needs in the golden child foundation.Children with special needs are children with different special characteristicsgenerally without always showing mental, emotional or physical disability Childrenwith special needs remain eligible for treatment and are considered the same asnormal children in general. Children with special needs require the role ofinterpersonal communication of teachers in building confidence of children so as tohave the confidence in interacting with normal people and new environment.This research uses interpretive approach. The research method used isqualitative method with descriptive level. Therefore, to meet the existing data,researchers chose informants in this study are teachers and guardians of students inthe golden children's foundation. Selection of informants by using purposive samplingtechnique. While data collection techniques through interviews and observationThe results of this study indicate that the interpersonal communication ofteachers to students in learning and playing activities are delivered verbally or nonverbally well established where the teacher focuses on giving spirit and praise toprovide motivation and foster self-confidence of children.